МЕХАНІЗМ ФОРМУВАННЯ МІСЬКОЇ ПОЛІТИКИ РЕАЛІЗАЦІЇ ТРУДОВОЇ АКТИВНОСТІ НАСЕЛЕННЯ - Druzhinina, V.V. (Економіка та право, 2008)
Essence of population labour activity is considered as an important self_regulator of the labour market flexibility. The forms of the local labour market flexibility have been analysed. The sphere of activity for local bodies is outlined, it indudes formation of city policy to realize the population’s labour activity.